Endoparasites of small mammals from northeastern Peru. 1: Helmintes of marsupials - Tantaleán, Manuel (2010)
In this paper, we report the results of parasitological examination performed on 40 specimens of marsupials species: Caluromys lanatus, Didelphis marsupialis, Marmosops noctivagus, Metachirus nudicaudatus, Marmosa (Micoureus)regina, Monodelphis adusta, Philander andersoni and Philander opossum from department of Loreto, Peru. The endoparasites were: Nematoda: Aspidodera sp., Cruzia tentaculata, Physaloptera mirandai, Physaloptera sp., Pterygodermatites sp., Trichuris sp., Turgida turgida, and Viannaia sp.; Trematoda: Podo- spathalium pedatum; Acanthocephala: Giganthorhynchus ortizi and Pentastomida: nymph. For the first time Trichuris sp., Pterygodematities sp., Turgida turgida, Viannaia sp. and Podospathalium pedatum are reported from marsupials in Peru. Also, for the first time the following parasite-hosts associations are recorded: Pterygo- dermatites sp.-Marmosa regina, Viannaia sp.-Marmosops noctivagus, Trichuris sp.-Marmosops cf. noctivagus, Podospathalium pedatum-Monodelphis adusta, Giganthorhynchus ortizi-Marmosops cf. noctivagus, and nymphs of pentastomida-Marmosa regina and Metachirus nudicaudatus.